Find the value of
tan⁻¹(√3) - sec⁻¹(-2)
Answers
Answered by
1
We know that the principal value branch of
![{tan}^{ - 1} \: [\frac{ - \pi}{2} ,\frac{\pi}{2} ]\\ {tan}^{ - 1} \: [\frac{ - \pi}{2} ,\frac{\pi}{2} ]\\](https://tex.z-dn.net/?f=+%7Btan%7D%5E%7B+-+1%7D+%5C%3A+%5B%5Cfrac%7B+-+%5Cpi%7D%7B2%7D+%2C%5Cfrac%7B%5Cpi%7D%7B2%7D+%5D%5C%5C+)
![{sec}^{ - 1} \: \: [0 ,\: \pi] - (\frac{\pi}{2})\\ {sec}^{ - 1} \: \: [0 ,\: \pi] - (\frac{\pi}{2})\\](https://tex.z-dn.net/?f=+%7Bsec%7D%5E%7B+-+1%7D+%5C%3A+%5C%3A+%5B0+%2C%5C%3A+%5Cpi%5D+-+%28%5Cfrac%7B%5Cpi%7D%7B2%7D%29%5C%5C+)
now
![{tan}^{ - 1} ( \sqrt{3} ) = \alpha \\ \\ then \\ \\ tan( \alpha ) = \sqrt{3} = tan( \frac{\pi}{3} ) \\ \\ where \: \frac{\pi}{3} \: belongs \: to \: [\frac{ - \pi}{2} ,\frac{\pi}{2}] \\ {tan}^{ - 1} ( \sqrt{3} ) = \alpha \\ \\ then \\ \\ tan( \alpha ) = \sqrt{3} = tan( \frac{\pi}{3} ) \\ \\ where \: \frac{\pi}{3} \: belongs \: to \: [\frac{ - \pi}{2} ,\frac{\pi}{2}] \\](https://tex.z-dn.net/?f=%7Btan%7D%5E%7B+-+1%7D+%28+%5Csqrt%7B3%7D+%29+%3D+%5Calpha+%5C%5C+%5C%5C+then+%5C%5C+%5C%5C+tan%28+%5Calpha+%29+%3D+%5Csqrt%7B3%7D+%3D+tan%28+%5Cfrac%7B%5Cpi%7D%7B3%7D+%29+%5C%5C+%5C%5C+where+%5C%3A+%5Cfrac%7B%5Cpi%7D%7B3%7D+%5C%3A+belongs+%5C%3A+to+%5C%3A+%5B%5Cfrac%7B+-+%5Cpi%7D%7B2%7D+%2C%5Cfrac%7B%5Cpi%7D%7B2%7D%5D+%5C%5C+)
So as
![{sec}^{ - 1} ( - 2) = \beta \\ \\ then \\ \\ \sec( \beta ) = - 2= - sec( \frac{\pi}{3} ) \\ \\ = sec(\pi - \frac{\pi}{3} ) \\ \\ = sec (\frac{2\pi}{3}) \\ \\ where \: \frac{2\pi}{3} \: belongs \: to \: \: \: [0 ,\: \pi] - (\frac{\pi}{2} )\\ {sec}^{ - 1} ( - 2) = \beta \\ \\ then \\ \\ \sec( \beta ) = - 2= - sec( \frac{\pi}{3} ) \\ \\ = sec(\pi - \frac{\pi}{3} ) \\ \\ = sec (\frac{2\pi}{3}) \\ \\ where \: \frac{2\pi}{3} \: belongs \: to \: \: \: [0 ,\: \pi] - (\frac{\pi}{2} )\\](https://tex.z-dn.net/?f=%7Bsec%7D%5E%7B+-+1%7D+%28+-+2%29+%3D+%5Cbeta+%5C%5C+%5C%5C+then+%5C%5C+%5C%5C+%5Csec%28+%5Cbeta+%29+%3D+-+2%3D+-+sec%28+%5Cfrac%7B%5Cpi%7D%7B3%7D+%29+%5C%5C+%5C%5C+%3D+sec%28%5Cpi+-+%5Cfrac%7B%5Cpi%7D%7B3%7D+%29+%5C%5C+%5C%5C+%3D+sec+%28%5Cfrac%7B2%5Cpi%7D%7B3%7D%29+%5C%5C+%5C%5C+where+%5C%3A+%5Cfrac%7B2%5Cpi%7D%7B3%7D+%5C%3A+belongs+%5C%3A+to+%5C%3A+%5C%3A+%5C%3A+%5B0+%2C%5C%3A+%5Cpi%5D+-+%28%5Cfrac%7B%5Cpi%7D%7B2%7D+%29%5C%5C)
now
tan⁻¹(√3) - sec⁻¹(-2) =
now
So as
now
tan⁻¹(√3) - sec⁻¹(-2) =
Similar questions
India Languages,
8 months ago
Political Science,
8 months ago
Math,
1 year ago
Social Sciences,
1 year ago
Biology,
1 year ago
English,
1 year ago